PENGEMBANGAN WIRAUSAHA DAN GREEN ECONOMY DI INDONESIA - Muhamad Aldo Efrenza (Universitas Mitra Indonesia, 2023)
The purpose of this study is to determine Entrepreneurial Development and Green Economy in Indonesia. The data used in this study is secondary data. Furthermore, the method used is this research using analytic observational research using a case control or case control research design. This research is included in the type of research that uses a qualitative approach and the analysis in this study is included in the type of descriptive research. Descriptive research seeks to describe, write, and report a situation, an object or an event as it is, and in the form of disclosing facts. Research containing entrepreneurship for environmental interests needs to be implemented in the business competition law system in Indonesia for various reasons, namely to reduce the adverse effects of climate change in Indonesia, increase and promote Green Economy in business transactions in Indonesia, provide legal certainty and legal benefits to companies and stakeholders who want to make agreements that prioritize green economy. Keywords : Entrepreneur, and Green Economy